Pengaruh Kemandirian Belajar, Gender, dan Keyakinan Matematika terhadap Pembuktian Matematika - Yuliana, Wahyu; Waluyo, Mohamad (Edumatica : Jurnal Pendidikan Matematika, 2024)
This research aims to determine the influence of learning independence, gender, and mathematical beliefs on mathematical proof. This research uses a survey method with correlational analysis. The population in this study were students from one of the Ngawen 1 High Schools and sampling using the Purposive Sampling technique for this research was students in classes X.6, X.8, and XI.9. The instruments used are mathematics proof tests and non-test instruments in the form of independence learning questionnaires and mathematics beliefs questionnaires using the Linkert Scale. Data analysis was carried out using the SPSS 23.0 program, consisting of descriptive analysis, data analysis prerequisite tests, and hypothesis testing. This research concludes that together learning independence, gender, and mathematical beliefs have an effect on mathematical proofs, learning independence has a positive effect on mathematical proofs, gender has no effect on mathematical proofs, mathematical beliefs have no effect on mathematical proofs, students in class X.6, X.8 and XI.9 SMA N 1 Ngawen.